Policy of Criminal System Formulation Oriented to Rape Crime Victims - Ahmad Syaufi; Diana Haiti (Sociological Jurisprudence Journal, 2018)
Criminal act of rape has received considerable attention among the public nowadays. The care and protection of the interests of the victims of the rape crime either through criminal justice process or certain social care facilities is an absolute part that needs to be considered in criminal law policies and social policies. Therefore, in the formulation of the criminal system, it is time to pay attention to the victim's interest to realize the equitable distribution of justice for the rights of rape victims to be protected. In the effort of developing and renewing the criminal law in Indonesia, it is necessary to conduct an assessment related to the policy of punishment formation system which is oriented to the rape crime victims in the coming criminal law. This study employed a qualitative research using normative law research design. In an effort to achieve the research objectives that have been determined, this study used statute approach and conceptual approach. Based on the results and discussion, policy formulation of punishment system that is oriented to rape crime victims in future criminal law is as follows: (1) in the material criminal law, protection of rape crime victims in its development is regulated in a Bill of Criminal Law, including the formulation of passive national principles, the extension of the concept of criminal acts of rape, and the formulation of types of sanctions. (2) in formal criminal law, the protection of victims, especially the rape crime victims, has been regulated in a Bill of Criminal Procedure Law, with the granting of procedural rights such as the right of a translator and the right of reimbursement of expenses. It is because legal protection against victims of rape crime is in need of services such as psychosocial, medical, and safe house.